IMPUNITY AND THE ELUDING PEACE IN NIGERIA: A PHILOSOPHER’S PANACEA - Udisi, Ebikisei Stanley; Ekperi, Mark (Universitas Negeri Makassar, 2024)
Impunity, defined as the exemption from punishment for acts that harm individuals or society, remains a critical challenge in nations where the rule of law is weak. It manifests through the failure to prosecute human rights violators and criminal offenders, often due to systemic corruption, weak judicial institutions, and entrenched patronage networks. In Nigeria, persistent social unrest and the absence of peaceful coexistence stem largely from the culture of impunity, where offenders evade justice and are sometimes celebrated rather than punished. This breakdown of societal values exacerbates insecurity and erodes public trust in governance. This paper critically examines Nigeria’s sociopolitical landscape, arguing that impunity is the primary driver of the nation’s cyclical security crises. Drawing from philosophical and legal perspectives, the study posits that the effective enforcement of the rule of law is indispensable in addressing Nigeria’s security challenges. By advocating for institutional reforms, judicial independence, and accountability mechanisms, this paper proposes a philosophical panacea to impunity and its attendant crises.